Interreligious dialogue from religion to geopolitics - Giordan, Giuseppe, (Annual Review of the Sociology of Religion, 2019)
Interreligious Dialogue: From Religion to Geopolitics discusses how interreligious dialogue takes place within, and is influenced by, important sociological categories and theories, such as modernity, secularization, deprivatization, social movements, and pluralism. Starting from the study of interreligious coexistence, sacred spaces, and multi-religious rituals, the book explores the patterns of interreligious governance and politics and forms of interreligious social action in European, North American, and West and South Asian contexts. The contributors to this volume apply broader theories of organizational change and planning, communication, urban neighborhood and community studies, functionalist perspectives, and symbolic interactionism, thus presenting a wide range of possibilities for sociological engagement with studies on interreligious dialogue.